The Role of Technology in Improving K-12 School Safety - Schwartz, Heather L. (RAND Corporation, 2016)
The report categorizes school safety technologies, noting the lack of research about school safety technology and summarizing the existing research on school violence; presents six case studies of innovative technologies used in schools; and summarizes experts' views of technologies and safety problems, determined through interviews; and presents experts' rankings of technology needs to improve school safety, produced during two day-long panels.